Editorial - Mani Man Singh Rajbhandari (Journal of Interdisciplinary Sciences)
Dear Readers, It is our immense pleasure to announce that the Journal of Interdisciplinary Sciences (JIS) is now indexed in the DOAJ: Directory of Open Access Journals. JIS is also indexed in JUFO: Julkaisufoorumi and NSD- Norwegian Register for Scientific Journals, Series and Publishers. As we commit ourselves to serving the academic and scientific communities, the purpose of serving has deepened even more for “Enriching Beautiful Minds towards Intelligent Minds” in a greater meaning. As we have struggled to reach this far since 2017, we are now even determined to walk extra miles. This encouragement comes from the authors and reviewers who have trusted in our confidence, intelligence, and fairness. In this volume 9, issue 1 of May 2025, we have published scientific papers from various disciplines and different countries. These published papers are openly accessible to all readers and uploaded to DOAJ and other indexing platforms. Submission to JIS is welcome from authors from all subjects. We look forward to more participation to Enrich the Beautiful Minds towards Intelligent Minds. Thank you very much Let us join and collaborate together to ENRICH the BEAUTIFUL MINDS TOWARDS INTELLIGENT MINDS Mani Man Singh Rajbhandari. Ph.D. Founder and Editor-in-Chief Journal of Interdisciplinary Sciences (JIS) www.journalofinterdisciplinarysciences.com